2020
DOI: 10.1111/epi.16485
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting cycles of seizure likelihood

Abstract: Objective: Seizure unpredictability is rated as one of the most challenging aspects of living with epilepsy. Seizure likelihood can be influenced by a range of environmental and physiological factors that are difficult to measure and quantify. However, some generalizable patterns have been demonstrated in seizure onset. A majority of people with epilepsy exhibit circadian rhythms in their seizure times, and many also show slower, multiday patterns. Seizure cycles can be measured using a range of recording moda… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 51 publications
1
87
0
Order By: Relevance
“…35 Importantly, forecasting algorithms based on multiday cycles have emerged as the most accurate, recently surpassing all previous approaches on a benchmark human dataset 6 as well as showing excellent performance for larger cohorts, 36 and using data from seizure diaries. 23 If heart rate can be shown to reliably track multiday cycles of seizure likelihood, then similarly powerful seizure forecasts may eventually be derived from wearable devices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…35 Importantly, forecasting algorithms based on multiday cycles have emerged as the most accurate, recently surpassing all previous approaches on a benchmark human dataset 6 as well as showing excellent performance for larger cohorts, 36 and using data from seizure diaries. 23 If heart rate can be shown to reliably track multiday cycles of seizure likelihood, then similarly powerful seizure forecasts may eventually be derived from wearable devices.…”
Section: Discussionmentioning
confidence: 99%
“…We had previously demonstrated that multiday cycles established from seizure diaries align with cycles recorded from true electrographic seizures. 23 Nevertheless, it will be critical to validate the co-modulation of heart rate cycles and epileptic activity using chronic EEG recordings. Future work will extend these results to validate the existence of multiday heart rate cycles and their relationship to electrographic seizures using ultra long-term EEG and additional wearable physiological sensors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The probability forecast, though obviously more informative than a binary forecast, will likely be degraded to a binary forecast when algorithms are written to initiate responsive neurostimulation ( 8 ). Even binary forecasting systems (high- and low-risk), using only patient-reported seizure data, correctly predicted seizures in about half of 50 patients ( 125 ).…”
Section: Background For Understanding Seizure Generation Inhibition and Propagationmentioning
confidence: 99%
“…This case study demonstrates how cycles can be derived from events in the EEG and in turn, these cycles can be used to forecast epileptic seizures. The forecasting method has been built on previous work in seizure cycles (20,(29)(30)(31) and interictal EA cycles (17,18,32).…”
Section: Introductionmentioning
confidence: 99%